Analisis Strategi Komunikasi Pemasaran Bisnis B2B Jasa Kalibrasi PT Mandiri Global Akurasi - Riki Khoerul Anwar; Dani Setiadarma (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the development of marketing communication strategies to build brand awareness at PT Mandiri Global Akurasi, a B2B calibration services company facing a sharp decline in revenue (69.6% in 2024 and 45% in 2025) and unstable client turnover. Using a constructivist paradigm with a qualitative case study approach, this study explores the subjective understandings of marketing managers, salespeople, administrative staff, and clients regarding their marketing communication practices. The findings reveal fundamental differences in the meaning of marketing communication. Management constructs it as a short-term acquisition instrument with quantitative targets (20 calls/emails per day). Clients interpret it as proof of professionalism and a foundation for long-term trust, with indicators such as speed of response, technical clarity, and post-sales attention. The CRM Practice Manual reflects the construction that client data is understood as administrative, not strategic assets. The process of constructing reality occurs through daily interactions: when salespeople explain calibration procedures, management interprets it as "selling," while clients interpret it as "proof of competence." Agreements at the practical level obscure differences in meaning, so that relationships remain transactional. As a result, the sharp increase in revenue was constructed by management as a "market problem," when in fact, its root was a misalignment of meanings about the nature of marketing communications. This research shows that marketing communications strategies are the result of social constructions negotiated through interaction, not realistic goals. Long-term performance stability requires shared meaning between management and clients. In the B2B calibration services industry, the shift from transactional to relational communication constructions opens the door to building loyalty and recurring revenue.